Reseña de D. A. Hernández de la Fuente (2023), Prolegómenos a una ciencia de la Antigüedad, Madrid: Síntesis, 190 págs. ISBN: 9788413572383 - Diez Adán, Carlos (Panta Rei. Revista digital de Historia y Didáctica de la Historia, 2024)
The present work pretends to review the book Prolegómenos a una ciencia de la Antigüdad by David Hernández de la Fuente, which is a little introduction that makes a full journey through the historiographical evolution of the classic studies of the History.